Investigating Knowledge and Attitude of Nursing Students Towards Iranian Traditional Medicine: Case Study: Universities of Tehran in 2012-2013 - Khorasgani, Sahar Rabani (Glob J Health Sci, 2014)
The present study aimed at Investigating the knowledge and attitude of Nursing Students towards Iranian Traditional Medicine in universities of Tehran in 2012-2013. 300 students of nursing studying at different universities in Tehran participated in this descriptive, cross-sectional study. The data was collected through a standard questionnaire with an acceptable validity and reliability. The questionnaire was made of five sections including demographic, general knowledge of the Iranian traditional medicine, general attitude towards it, resources of the Iranian traditional medicine and the barriers to it. The results revealed that general knowledge of the students about Iranian traditional medicine and complementary medicine is low. The attitude of the students towards including Iranian traditional medicine and complementary medicine in their curriculum is positive. General attitude of students towards Iranian traditional medicine is positive too. The majority of the participants had not passed any course on Iranian traditional medicine. There was no relationship between participants’ attitude towards Iranian traditional medicine and the number of semesters they had passed. Considering the participants’ positive attitude and their low level of knowledge, it seems necessary for the university policy makers to provide nursing students with different training courses on Iranian traditional medicine and complementary medicine in order to increase their knowledge.